REDESAIN TAMAN KOTA ATAMBUA BERBASIS BUDAYA LOKAL - Neksen Bere, Huanda Gregorius; Setyabudi, Irawan; Nailufar, Balqis (Universitas Tribhuwana Tunggadewi, 2017)
The city of Atambua is the capital of Belu district, has many tourism potential, one of which is the Garden City of Atambua which is located in the middle of the city close to the settlement, offices, times talau, tennis general, and senggol market. Early development of the city park Atambua many visitors, by constructing the city facilities such as Plaza Atambua, make people more and more people visit the site compared to the city park in Atambua. The condition is caused by the lack of supporting facilities in the garden make visitors feel bored, modular garden design and does not follow the changes in the behavior of the society that the more modern, lack the characteristic of the garden so that the garden is not functional. For that we need to restore the city park Atambua as a landmark in Atambua with local culture as the characteristic of the garden, and designed with the adjectives adjust the urban life. The method used to design by modifying the method Rustam Judges (2012) and Gold (1980) and produce modern design using the concept of local culture. Kota Atambua adalah Ibukota Kabupaten Belu, mempunyai banyak potensi wisata, salah satunya adalah Taman Kota Atambua yang terletak di tengah-tengah Kota, yang dekat dengan pemukiman, perkantoran, kali talau, lapangan umum, dan pasar senggol. Awal pembangunan Taman Kota Atambua ramai pengunjung, dengan dibangunnya fasilitas kota seperti Plaza Atambua, membuat orang lebih ramai mengunjungi tempat tersebut dibandingkan Taman Kota Atambua. Kondisi tersebut disebabkan oleh kurangnya fasilitas pendukung didalam taman membuat pengunjung merasa bosan, desain taman yang modular dan tidak mengikuti perubahan perilaku masyarakat yang semakin modern, tidak adanya ciri khas dari taman sehingga taman tidak fungsional. Untuk itu perlu mengembalikan Taman Kota Atambua sebagai landmark Kota Atambua dengan budaya lokal sebagai ciri khas taman, dan didesain dengan bentukan yang menyesuaikan kehidupan masyarakat urban. Metode yang dipakai untuk mendesain yaitu dengan memodifikasi metode Rustam Hakim (2012) dan Gold (1980) dan menghasilkan desain modern dengan mengunakan konsep budaya lokal.